Giant panda seasonal adaptations in feeding strategies and blood physiology - Gu, Jiang; Yu, Xiang; Qi, Dunwu; Hou, Rong; Zhang, Long; Lan, Guanwei; Feng, Feifei; Bi, Wenlei; Xue, Fei; Liu, Jiabin; Huang, Chong; Li, Zusheng; et al. (Frontiers in Veterinary Science, 2025)
Understanding physiological adaptations of endangered giant pandas to seasonal changes is critical for improving conservation efforts, yet integrated analyses of blood parameters and feeding strategies remain limited. To decode seasonal adaptation mechanisms, we analyzed 36 monthly blood samples from 3 female pre-released training pandas alongside bamboo components across winter–spring and summer-autumn. Results showed significantly higher lymphocyte counts and urea levels, but lower serum aspartate aminotransferase, serum alkaline phosphatase, glucose and lipase in summer-autumn. Correspondingly, pandas consumed significantly more hemicellulose, crude ash, crude protein and minerals (e.g., potassium, calcium, magnesium, phosphorus, manganese, chromium, copper and zinc) in summer and autumn, while greater intake of starch, lignin, cadmium in winter–spring, reflecting a shift from stems to leaves. Key blood parameters correlated with bamboo component intake. These findings indicate a nutrient-driven strategy favoring anabolic metabolism in resource-rich seasons, providing physiological thresholds for improved conservation and release programs.